2011
DOI: 10.4067/s0717-92002011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la exposición y la toposecuencia sobre actividades biológicas del suelo en bosque relicto del centro-sur de Chile

Abstract: SUMMARYCatastrophic disturbances of forest ecosystems are natural and anthropogenic phenomena that promote the natural dynamics of biocenosis and biogeochemical processes, and are the main causes of landscape fragmentation. The aim of this study was to evaluate the effect of orientation and toposequential positions on some biological activities in a relict forest community of LapagerioAextoxiconetum during two seasons. Soil samples were collected from an Andisol (0-15 cm), for each toposequential position (hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…This activity diminished with depth (20-40 cm) to values of 86.3-198.1 mg N-NH 4 g -1 h -1 . The observed decrease of UR activity with increasing soil depth may be related to a minor temperature (Reyes et al, 2011). The UR activity values for PC 0-20 cm depth, were higher during the whole sampling period, as compared with P1 and P2 (Figure 3).…”
Section: Soil Enzymes Activitiesmentioning
confidence: 85%
See 1 more Smart Citation
“…This activity diminished with depth (20-40 cm) to values of 86.3-198.1 mg N-NH 4 g -1 h -1 . The observed decrease of UR activity with increasing soil depth may be related to a minor temperature (Reyes et al, 2011). The UR activity values for PC 0-20 cm depth, were higher during the whole sampling period, as compared with P1 and P2 (Figure 3).…”
Section: Soil Enzymes Activitiesmentioning
confidence: 85%
“…The soil enzymes activities are an integrating indicator of the biological activity and the physical and chemical conditions, which permits the evaluation of the microbial capacity in the catalytic processes, as well as the availability of nutrients by means of enzymatic processes (Reyes et al, 2011;Cardoso et al, 2013). The importance of certain soil enzymes has been described, such as catalase, cellulase and urease, serving as indicators of the biological activity of the soil in the event of alterations (García and Hernández, 1997;Smethurst et al, 1998;Saviozzi et al, 2001;Levi-Minzi et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of U RS , the higher C and N biomass in the SPS (M SOC M N ) may stimulate the FDA activity [72], which may explain the differences that were observed mainly at the 5-20 depth between systems. In Andisols (0-15 cm), from a relict-native forest consisting of the plant associations: Aextoxicon punctatum, Nothofagus obliqua,Eucryphia cordifolia, Laurelia sempervirens and Persea lingue in Temuco, Chile, Reyes et al [74] observed similar trends to our findings in M SOC (1245 µg C g dw −1 ), M N (99.5 µg N g dw −1 ), and FDA (51.5 µg F g dw −1 ), although there were remarkable differences for β-GLU and P HOSP activities, with means of 7.3 and 68.2 µmol g dw −1 h −1 PNF, respectively, virtually tripling and exceeding by a 10 order of magnitude our measurements. This may be related to the maturity stage of the forest, compared with our study sites.…”
Section: Microbiological Properties As Si Ndsmentioning
confidence: 99%
“…Los cafetales producidos como monocultivo y a pleno sol pueden incrementar sus rendimientos por la incorporación de los fertilizantes, pero a costa de la sustentabilidad del suelo que poco a poco se merma y la actividad de la biota también (Guerrero et al, 2012). Las modificaciones edafológicas son un factor que puede aumentar o disminuir la actividad microbiana y la respiración (Reyes et al, 2011). Debido a que la calidad del suelo ya no puede estudiarse con un componente aislado, es necesario entender el recurso suelo como un sistema vivo dinámico que tiende a estar en equilibrio bajo la interacción de factores físicos, químicos y biológicos (Paz-Ferreiro y Fu, 2013).…”
Section: Cuadrounclassified